The creation and implementation of an outpatient pulmonary embolism treatment protocol. Issue 3 (27th May 2017) - Kabrhel, Christopher; Rosovsky, Rachel; Baugh, Christopher; Parry, Blair Alden; Deadmon, Erin; Kreger, Charlotte; Giordano, Nicholas
ABSTRACT: The ability to rapidly and accurately risk-stratify patients with venous thromboembolism (VTE), and the availability of direct acting oral anticoagulants have reduced the need for intravenous anticoagulation for patients with deep vein thrombosis (DVT) and pulmonary embolism (PE). Emergency physicians are generally reluctant to discharge patients with VTE without defined and reliable follow up in place, and VTE patients treated with anticoagulants can be at risk for complications related to recurrent VTE and bleeding. In addition, screening for associated diseases (e.g. cancer, hypercoagulable states) may be indicated. Therefore, the outpatient treatment of low risk VTE requires coordinated effort and reliable follow up. By leveraging detailed outcome data and collaborative relationships, we have created a protocol for the safe outpatient treatment of patients with low risk DVT and PE. Our protocol is data driven and designed to address barriers to outpatient VTE management. We expect our protocol to result in improved patient satisfaction, more efficient emergency department (ED) throughput, and decreased cost. Applied nationally, the outpatient treatment of select patients with DVT and PE could have major public health and economic impact.